PENGETAHUAN DAN SIKAP KESIAPSIAGAAN ANAK USIA SEKOLAH SETELAH DIBERIKAN SIMULASI GEMPA BUMI - Tiya Rama Fitri; Rahmi Muthia; Mohd. Djamil (Universitas Prima Indonesia, 2023)
Due to children's lack of knowledge and attitudes about how to save themselves during an earthquake, school-age children are one of the vulnerable groups who become the most victims during an earthquake. One of the efforts to minimize victims of school-age children during an earthquake is to provide self-rescue simulation training during an earthquake. This study aimed to describe the knowledge and attitude preparedness of school-age children in the face of an earthquake after being given a simulation of self-rescue during an earthquake in RW 02, Kelurahan Pasia Nan Tigo. This type of research is descriptive with a quantitative approach. The sample in this study amounted to 32 school-age children using the total sampling technique. The data was collected by spreading questionnaires of knowledge and attitudes about self-rescue preparedness during an earthquake by LIPI/UNESCO/ISDR in 2006. The results showed that almost all School-age children understood self-rescue preparedness during an earthquake (84.4%), and most of them had positive behavior (75%). The recommended that the member of RW 02 Kelurahan Pasia Nan Tigo could collaborate with BPBD Padang City to hold regular self-rescue drills or simulations during earthquakes.